2014
DOI: 10.1017/s1049023x14001289
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Coma Scale Scoring is Often Inaccurate

Abstract: Glasgow Coma Scale scoring should not be considered accurate. A more simplified scoring system should be developed and validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 21 publications
(54 reference statements)
2
70
0
1
Order By: Relevance
“…42 Further, scoring of GCS may be compromised in patients who are intubated and sedated, and in an acute setting has lower inter-rater reliability. 43 These factors may explain why we did not observe differences in tau levels by injury severity. However, our study showed a relationship of tau levels with injury severity by demonstrating a correlation between duration of PTA and Day 30 tau, and between injury severity by Marshall Grade and tau levels at Day 30.…”
mentioning
confidence: 81%
“…42 Further, scoring of GCS may be compromised in patients who are intubated and sedated, and in an acute setting has lower inter-rater reliability. 43 These factors may explain why we did not observe differences in tau levels by injury severity. However, our study showed a relationship of tau levels with injury severity by demonstrating a correlation between duration of PTA and Day 30 tau, and between injury severity by Marshall Grade and tau levels at Day 30.…”
mentioning
confidence: 81%
“…Another limitation is the heterogeneity of our cohort, comprising of mild-to-severe TBI cases (see Supplementary Table S1). TBI severity has historically been categorized using GCS, however GCS has obvious limitations in its subjectivity (Bledsoe et al, 2014) and the fact that the patients may be sedated (Stocchetti et al, 2004). In the current study, TBI patients in need of neuro-intensive care for their head injuries were included which we believe represents a clinically valid and reproducible cohort of TBI patients and as can be seen by the AIS, all suffered from structural severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to determine how accurately emergency department healthcare professionals can determine the GCS in simulated patient encounters (Bledsoe et al . ) prospective observational American study of the accuracy of GCS scoring found out of a total of 2084 GCS observations the overall accuracy was 33·1%. Specifically, the verbal, eye‐opening and motor scores were only accurate and correct in 69, 61·2 and 59·8% of assessments respectively.…”
Section: Methodsmentioning
confidence: 99%